A novel matlab/simulink model of DFIG drive using NSMC method with NSVM strategy - Habib Benbouhenni; Zinelaabidine Boudjema; Abdelkader Belaidi (Institute of Advanced Engineering and Science, 2019)
In this article, we present a comparative study between pulse width modulation (PWM) and neural space vector modulation (NSVM) strategy associated with a neuro-sliding mode control (NSMC) of stator reactive and stator active power command of a doubly fed induction generator (DFIG). The obtained results showed that, the proposed NSMC with NSVM strategy have rotor current with low harmonic distortion and low powers ripples than PWM strategy.